EP865 Forkhead box protein O1 and Paired box gene 3 overexpression is associated with poor prognosis in patients with epithelial ovarian cancer. (1st November 2019) - Cho, H; Han, GH; Chay, DB; Kim, S; Kim, J-H
Abstract : Introduction/Background: Transcriptional factor FOXO1and PAX3 has been reported to play an imported role in human cancer, but the role in epithelial ovarian cancer (EOC) has not yet been clarified. Here, we evaluated the functional role and expression of FOXO1 with EOC tissues with clinical significance of FOXO1 and PAX3 in EOC. Methodology: In vitro assessment of cell functions by cell viably assay, cell migration and invasion assay was evaluated using FOXO1 knockdown EOC cell lines. Immuno-histochemical (IHC) staining analyses of FOXO1 and PAX3 were performed using tissue microassay analysis of 141 EOC, 139 borderline ovarian tumors and 48 benign epithelial ovarian tumors and 161 nonadjacent normal epithelial tissues and the data were compared with clinicopathological variables, including the survival of ovarian cancer patients. Results: In vitro result revealed that knockdown of FOXO1 was associated decreased cell viability ( p <0.001), migration ( p <0.001) and invasion ( p <0.05) supporting the oncogenic role of FOXO1 in EOC. Expressions of FOXO1 and PAX3 were significantly increased in ovarian cancer tissues than in normal epithelium (both p <0.001). Immunoreactivity of FOXO1 significantly correlated with cell type ( p <0.001). FOXO1 expression showed strong positive correlation with that of PAX3 (Spearman's rho=0.430, p <0.001) in cancer patients. Using cox proportional hazards model, we found FOXO1 expression (hazard ratio=4.01 [95% CI, 1.22–13.10], p =0.021) and advanced FIGO stage (hazard ratio=3.89 [95% CI, 1.35–11.19], p =0.012) were independent prognostic factors on overall survival. Conclusion: This study reveals the association between FOXO1 and PAX3 expression with clinicopathologic variables, including survival of EOC patients. Our results not only suggest the promising potential of FOXO1 as a prognostic and survival marker, but also warrant further studies on a possible link between the biological function of FOXO1 and the pathogenesis of EOC. Disclosure: Nothing to disclose.